Capital Gains Taxes and Acquisition Activity: Evidence of the Lock‐in Effect* - Ayers, Benjamin C.; Lefanowicz, Craig E.; Robinson, John R. (Contemporary Accounting Research, 2007)
The lock-in effect proposes that capital gains taxes represent transaction costs that increase the reservation price for security owners and, ceteris paribus, reduce trading volume. Consistent with the lock-in effect, previous empirical research documents price and reactions to enacted changes in the capital gains tax rate. We investigate whether the volume hypothesis predicted by the lock-in effect extends to corporate acquisition activity. In particular, we analyze whether aggregate corporate acquisition activity is inversely associated with shareholder capital gains tax rates. We measure quarterly corporate acquisition activity from 1973 through 2001 using (1) the percentage of traded firms acquired in a calendar quarter and (2) the percentage of market value of traded firms acquired in a calendar quarter. In supplemental analysis, we measure acquisition activity at the industry level (i.e., as the percentage of firms and percentage of market value acquired by industry annually). In each analysis we model acquisition activity as a function of the maximum long-term capital gains tax rate for individuals and other macroeconomic factors previously hypothesized to be associated with acquisition activity. Consistent with a lock-in effect for corporate acquisitions, we find a significant negative association between corporate acquisition activity and the capital gains tax rate whether we measure acquisition activity in the aggregate or at the industry level. In addition, we find that this negative association is attributable to increased (decreased) taxable acquisition activity during periods of low (high) capital gains tax rates. These results suggest that, ceteris paribus, capital gains taxes represent significant transaction costs that influence the level of corporate acquisition activity.